ҚАРАҚАЛПАҚ ХАЛЫҚ НАҚЫЛ-МАҚАЛЛАРЫНЫҢ ЖАНРЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Жиемуратова, Ф.Е. (FAN va JAMIYAT, 2025)
The article examines and analyzes the genre features of Karakalpak folk proverbs in all aspects. He touched upon the cultural, national, and national essence of proverbs. All ideas are supplemented with examples.